2022
DOI: 10.1038/s41598-022-08974-8
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised machine learning for identifying important visual features through bag-of-words using histopathology data from chronic kidney disease

Abstract: Pathologists use visual classification to assess patient kidney biopsy samples when diagnosing the underlying cause of kidney disease. However, the assessment is qualitative, or semi-quantitative at best, and reproducibility is challenging. To discover previously unknown features which predict patient outcomes and overcome substantial interobserver variability, we developed an unsupervised bag-of-words model. Our study applied to the C-PROBE cohort of patients with chronic kidney disease (CKD). 107,471 histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…Previously, we have shown that unsupervised machine-learned clustering features are potential surrogates of predicting eGFR and can be used as tools for prognosis as well as for objective assessment of the level of kidney function in CKD 45 . In the present study, our results demonstrate that the addition of spatial information improves the model's performance by 2.4% and 5.1% of AUC at the biopsy and one-year prediction, respectively, compared to the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that unsupervised machine-learned clustering features are potential surrogates of predicting eGFR and can be used as tools for prognosis as well as for objective assessment of the level of kidney function in CKD 45 . In the present study, our results demonstrate that the addition of spatial information improves the model's performance by 2.4% and 5.1% of AUC at the biopsy and one-year prediction, respectively, compared to the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to cluster image patterns on image patches, we extracted features from each image patch for the clustering using pre-trained DeepLab V3+ with ResNet-18 model. 38,45 Then, all 172 biopsy cores on images were tiled into 107,471 patches. Then, those patches were clustered through K-means clustering to group similar image patterns together (Figure 3a).…”
Section: Unsupervised Machine Learning To Cluster Image Patterns Over...mentioning
confidence: 99%
“…Based on the comprehensive morphological features extracted from 161 renal biopsies, along with patient clinical information, the AUC of the prediction model for eGFR at biopsy time reached 0.93, while that for 1-year eGFR was 0.80. These results indicated the potential of visual-feature-based algorithms for predicting CKD progression [ 113 ].…”
Section: Application Of Ai In Nephropathologymentioning
confidence: 95%
“…The challenges in deep learning for cancer or disease diagnosis on histopathological images include the use of large amounts of accurately annotated data and the generalization limitations of WSIs due to multiple variants and the intricate cellular structure of histopathology data. Publicly available WSIs with accurate annotation or label information are fewer as compared to natural image datasets because acquiring WSIs is a difficult and costly task owing to the specific nature of medical imaging modalities [ 2 , 3 , 4 , 5 ]. To address this issue, previous researchers used pre-trained models based on previously acquired knowledge from different domain image datasets and then applied them to the medical imaging domain.…”
Section: Introductionmentioning
confidence: 99%